2005
DOI: 10.1097/00008483-200511000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Managing Chronic Obstructive Pulmonary Disease in the Community

Abstract: A 12-week home-based pulmonary rehabilitation is effective in improving exercise tolerance, perception of breathlessness, and quality of life for housebound COPD patients. To manage COPD in the community more effectively, health services should focus on expanding home-based pulmonary rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 26 publications
2
66
0
Order By: Relevance
“…There may be unobserved confounding despite propensity matching. Reductions in LOS after rehabilitation have also been reported in some RCTs 24,25 and observational studies 26 whereas a reduction in LOS was not observed in this cohort. Reasons for this may include the fact that patients in our analysis are older and frailer and possibly have more comorbidities than those who participated in the RCTs.…”
Section: Discussionsupporting
confidence: 74%
“…There may be unobserved confounding despite propensity matching. Reductions in LOS after rehabilitation have also been reported in some RCTs 24,25 and observational studies 26 whereas a reduction in LOS was not observed in this cohort. Reasons for this may include the fact that patients in our analysis are older and frailer and possibly have more comorbidities than those who participated in the RCTs.…”
Section: Discussionsupporting
confidence: 74%
“…Five studies were not examined; three studies were only available as English abstracts as the articles were published in Spanish,20 French,21 and Chinese 22. Boxall23 was not used in the form, ie, congress abstract, in which it was used in the Cochrane review, it was instead published as an article in 2006 24. Chlumsky 200125 was not found.…”
Section: Methodsmentioning
confidence: 99%
“…Table 7 summarises the type of interventions that were employed in the studies included in the review of complex interventions in COPD, and the duration of the intervention. 118,120,121,123,125,129,130,138,139,142,148 ), behaviour therapy (zero studies), relapse prevention (11 studies 117,118,121,124,127,129,132,135,140,144,147 ), problem-solving (zero studies), cognitive-behavioural therapy (CBT) (zero studies), increased social support (zero studies) and relaxation therapy (four studies 118,121,125,146 ). The forest plot for the meta-analysis is shown in Figure 12.…”
Section: Figure 11mentioning
confidence: 99%
“…Bergner 119 Bergner 119 Bourbeau 118 Boxall 120 Casas 114 Eaton 121 Farrero 122 Gadoury 123 Gallefoss 124 Güel 125 Hermiz 126 Hernandez 127 Jarab 128 Khdour 129 Ko 130 Koff 131 Lee 132…”
Section: -181mentioning
confidence: 99%